2001
DOI: 10.1007/bf02918291
|View full text |Cite
|
Sign up to set email alerts
|

Effects of (−)-epigallocatechin gallate (EGCG) on DNA strand breaks as evaluated by single-cell gel electrophoresis (SCG) in human lymphocytes

Abstract: (-)-Epigallocatechin gallate (EGCG), a catechin polyphenol component, is the main ingredient of green tea extract. Although the anti-carcinogenic and cancer inhibitory effects of EGCG have been widely reported, its genotoxicity is not clear and seldom reported. In this study, we examined the effects of EGCG on DNA strand breaks in the isolated lymphocytes and whole blood lymphocytes obtained from two smoking subjects and a nonsmoking healthy subject using a single cell gel electrophoresis (SCG) assay. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Several studies have demonstrated protective effects of epigallocatechin-3-gallate (EGCG), the predominant polyphenolic component of green tea, on the generation of DNA strand breaks in human lymphocytes (25)(26)(27). Therefore, the present study aimed to investigate the effects of BTE on DNA oxidative damage on human healthy lymphocytes, using a comet assay.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated protective effects of epigallocatechin-3-gallate (EGCG), the predominant polyphenolic component of green tea, on the generation of DNA strand breaks in human lymphocytes (25)(26)(27). Therefore, the present study aimed to investigate the effects of BTE on DNA oxidative damage on human healthy lymphocytes, using a comet assay.…”
Section: Discussionmentioning
confidence: 99%
“…Cooperative effect was observed when the anti-cancer, DNA binding compound bleomycin was used in conjunction with EGCG, showing a potentiated anti-proliferative effect in pancreatic cancer cells (Bimonte et al, 2015). Additionally, interaction of EGCG in single-strand DNA chains showed increased nuclease activity in whole blood and isolated lymphocytes cells (Yuquan, Takeshita, & Morimoto, 2001). Using surface plasmon resonance assays and cold spray ionization-mass spectrometry, Fujiki and collaborators found that EGCG binds to DNA and RNA polymers between 1:1 and 3:1 stoichiometry (Kuzuhara, Sei, Yamaguchi, Suganuma, & Fujiki, 2006).…”
Section: Introductionmentioning
confidence: 99%